Iodide capped PbS/CdS core-shell quantum dots for efficient long-wavelength near-infrared light-emitting diodes - Yang, Xuyong (2018)
PbS based quantum dots (QDs) have been studied in great detail for potential applications in electroluminescent devices operating at wavelengths important for telecommunications (1.3–1.6 μm). Despite the recent advances in field of quantum dot light-emitting diode (QLED), further improvements in near-infrared (NIR) emitting device performance are still necessary for the widespread use and commercialization of NIR emitting QLED technology. Here, we report a high-performance 1.51-μm emitting QLED with inverted organic–inorganic hybrid device architecture and PbS/CdS core-shell structured quantum dots as emitter. The resultant QLEDs show a record device performance for the QLEDs in 1.5 μm emission window, with a maximum radiance of 6.04 Wsr−1 m−2 and peak external quantum efficiency (EQE) of 4.12%, respectively.